Analisis Asuhan Keperawatan Bersihan Jalan Napas Tidak Efektif pada Anak Bronkopneumonia Dengan Tindakan Kolaborasi Pemberian Nebulizer di Ruang Picu Rsud Prof. Dr. H. Aloei Saboe - Dewi Modjo; Andi Akifa Sudirman; Silvana Djafar Ibrahim (Jurnal Rumpun Ilmu Kesehatan, 2023)
Background: Because of the very high mortality in children and children under the age of five, bronchopneumonia is the leading cause of death in children under the age of five worldwide. When viruses, bacteria, microbes and fungi enter the lungs through the respiratory system, they infect the lung parenchyma and cause pneumonia. Objective: Analyzing ineffective airway clearance nursing care in children with bronchopneumonia by collaborative action of administering a nebulizer in the Picu Room of Prof. Hospital. Dr. H Aloei Saboe Methods: Participants in this study, which used a quasi-experimental design, received treatment or intervention before measuring and analyzing the impacts. The pre-post-test group design method served as the basis for the research design. In children with bronchopneumonia, this strategy is used to check the results before and after administration of the nebulizer. Two young people who fight against crime become samples. Results: The results of the study show the overall evaluation results after nursing actions, namely: Based on the results before being given a nebulizer to patients the problem was not resolved in 2 patients and after being given a nebulizer to patients the problem was resolved in 2 patients Conclusion: Based on the description above, inhalation therapy to reduce symptoms of shortness of breath in children with bronchopneumonia is effective where inhalation therapy or steam inhalation therapy using drugs can widen the bronchial airways resulting in complaints such as shortness of breath and disappearance of breath sounds.